2015
DOI: 10.1155/2015/136595
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Intraoperative TEE to Assess Supraventricular Tachycardia-Inducing Right-Sided Cardiac Compression by the Liver, Post-Liver-Transplantation Status

Abstract: This unique and interesting case report involves a patient who recently underwent a combined liver and kidney transplant (due to autosomal dominant polycystic kidney disease) and subsequently suffered from episodes of supraventricular tachycardia (SVT) secondary to the new liver graft compressing the right atrium and ventricle. After this was diagnosed, the patient underwent operative plication of the right hemidiaphragm. Intraoperative transesophageal echocardiography was used to demonstrate cardiac compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Utilizing a ME bicaval view with a slight rightward turn and advancement of the probe, they were able to visualize and evaluate the “piggyback technique” of anastomoses following OLT. Stoll et al 15 in a case report described a unique view revealing the cause of recurrent supraventricular tachycardia due to extrinsic compression of the right atrium by the liver and diaphragm in a post-liver transplant case. In that case, a ME 4 chamber view, and a ME 5 chamber view with an omniplane angle of 70° were used to guide surgical plication of the diaphragm in real time, ultimately alleviating the recurrent supraventricular tachycardia.…”
Section: Resultsmentioning
confidence: 99%
“…Utilizing a ME bicaval view with a slight rightward turn and advancement of the probe, they were able to visualize and evaluate the “piggyback technique” of anastomoses following OLT. Stoll et al 15 in a case report described a unique view revealing the cause of recurrent supraventricular tachycardia due to extrinsic compression of the right atrium by the liver and diaphragm in a post-liver transplant case. In that case, a ME 4 chamber view, and a ME 5 chamber view with an omniplane angle of 70° were used to guide surgical plication of the diaphragm in real time, ultimately alleviating the recurrent supraventricular tachycardia.…”
Section: Resultsmentioning
confidence: 99%
“…This symptomatic myocardial compression by the liver was guided and confirmed via RT-TEE imaging with a successful resolution [50]. Even in obstetric surgery, Cho et al reported a rare case of abrupt hemodynamic instability in a woman during a vaginal hysterectomy, iTEE was performed and a right atrium thrombus was identified [51].…”
Section: Non Cardiac Surgerymentioning
confidence: 94%